Otonomi Khusus Papua dan Papua Barat: Gambaran Sejumlah Masalah Kunci - Hasibuan, Sarah (Bestuurskunde: Journal of Governmental Studies, 2022)
The special autonomy granted to the Provinces of Papua and West Papua is a special authority that is recognized and granted by the central government to the Provinces of Papua and West Papua to regulate and manage the interests of their local community based on the aspirations and basic rights of the people of Papua and West Papua.  The implementation of the special autonomy in Papua and West Papua has encountered many challenges, such as in managing funds, human resources, institutional capacity, and governance, which impacted the welfare of the people.  This study aimed to review the two decades of implementation of the special autonomy, its challenges and obstacles, and dynamics in fund supervision in improving the welfare of the people of Papua and West Papua. To achieve its aims, this study used a descriptive qualitative approach with a literature review. The results of the study showed that there were discrepancies in the use of special autonomy funds and low realization of the budget for education and health in the provinces of Papua and West Papua.  Even though there has been an increase in welfare in Papua, Papua was still lagging compared to other provinces as evident from its HDI and poverty levels. The slow political process, limited government personnel, and human resources contributed to the slow handling of conflicts in Papua and West Papua. Supervision of special autonomy funds faced many obstacles in the communication process, weak legal instruments, and weak coordination between the central government, regional government, and community.